Sexual Dimorphism in Hepatic, Adipose Tissue, and Peripheral Tissue Insulin Sensitivity in Obese Humans - ter Horst, Kasper W.; Gilijamse, Pim W.; de Weijer, Barbara A.; Kilicarslan, Murat; Ackermans, Mariette T.; Nederveen, Aart J.; Nieuwdorp, Max; Romijn, Johannes A.; Serlie, Mireille J. (Frontiers in Endocrinology, 2015)
Glucose and lipid metabolism differ between men and women, and women tend to have better whole-body or muscle insulin sensitivity. This may be explained, in part, by differences in sex hormones and adipose tissue distribution. Few studies have investigated gender differences in hepatic, adipose tissue and whole-body insulin sensitivity between severely obese men and women. In this study, we aimed to determine the differences in glucose metabolism between severely obese men and women using tissue-specific measurements of insulin sensitivity. Insulin sensitivity was compared between age and body mass index (BMI)-matched obese men and women by a two-step euglycemic hyperinsulinemic clamp with infusion of [6,6-2H2]glucose. Basal endogenous glucose production and insulin sensitivity of the liver, adipose tissue and peripheral tissues were assessed. Liver fat content was assessed by proton magnetic resonance spectroscopy in a subset of included subjects. We included 46 obese men and women (age, 48±2 vs 46±2 years, p=0.591; BMI, 41±1 vs 41±1 kg/m2, p=0.832). There was no difference in basal endogenous glucose production (14.4±1.0 vs 15.3±0.5 µmol•kg fat-free mass-1•min-1, p=0.410), adipose tissue insulin sensitivity (insulin-mediated suppression of free fatty acids, 71.6±3.6 vs 76.1±2.6%, p=0.314) or peripheral insulin sensitivity (insulin-stimulated rate of disappearance of glucose, 26.2±2.1 vs 22.7±1.7 µmol•kg-1•min-1, p=0.211). Obese men were characterized by lower hepatic insulin sensitivity (insulin-mediated suppression of endogenous glucose production, 61.7±4.1 vs 72.8±2.5% in men vs women, resp., p=0.028). Finally, these observations could not be explained by differences in liver fat content (men vs women, 16.5±3.1 vs 16.0±2.5%, p=0.913, n=27). We conclude that obese men have lower hepatic, but comparable adipose tissue and peripheral tissue, insulin sensitivity compared to similarly obese women. Hepatic insulin resistance may contribute to the higher prevalence of diabetes in obese men. Further insight into the mechanisms underlying this gender difference may reveal novel targets for diabetes prevention and/or therapy.